Gonadotropin-releasing hormone 2 suppresses food intake in the zebrafish, Danio rerio - Nishiguchi, Ryo; Azuma, Morio; Yokobori, Eri; Uchiyama, Minoru; Matsuda, Kouhei (Frontiers in Endocrinology, 2012)
Gonadotropin-releasing hormone (GnRH) is an evolutionarily conserved neuropeptide with 10 amino acid residues, of which several structural variants exist. A molecular form known as GnRH2 ([His5 Trp7 Tyr8]GnRH, also known as chicken GnRH II) is widely distributed in vertebrates except for rodents, and has recently been implicated in the regulation of feeding behavior in goldfish. However, the influence of GnRH2 on feeding behavior in other fish has not yet been studied. In the present study, therefore, we investigated the role of GnRH2 in the regulation of feeding behavior in a zebrafish model, and examined its involvement in food intake after intracerebroventricular (ICV) administration. ICV injection of GnRH2 at 0.1 and 1 pmol/g body weight (BW) induced a marked decrease of food consumption in a dose-dependent manner during 30 min after feeding. Cumulative food intake was significantly decreased by ICV injection of GnRH2 at 1 pmol/g BW during the 30-min post-treatment observation period. The anorexigenic action of GnRH2 was completely blocked by treatment with the GnRH type I receptor antagonist Antide at 50 pmol/g BW. We also examined the effect of feeding condition on the expression level of the GnRH2 transcript in the hypothalamus. Levels of GnRH2 mRNA obtained from fish that had been provided excess food for 7 days were higher than those in fish that had been fed normally. These results suggest that, in zebrafish, GnRH2 acts as an anorexigenic factor, as is the case in goldfish.